PENGARUH PENGGUNAAN MEDIA GRAFIS TERHADAP MINAT BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA KELAS VIII SMP NEGERI 4 TARUTUNG TAHUN 2018 - Andar Gunawan Pasaribu (Institut Agama Kristen Negeri Tarutung, 2018)
This Research aim to to know the Graphical Media Use To Enthusiasm Learn The Education of Christian of Student of Class of VIII SMP Negeri 4 Tarutung of North Tapanuli of Study Year 2018. with the hypothesizing [of] there are influence which are positive and signifikan [of] [among/between] Graphical Media Use To Enthusiasm Learn The Education of Christian of Student of Class of VIII SMP Negeri 4 Tarutung of North Tapanuli of Study Year 2018. Research population amount to 122 people and sampel amount to 61 people. Data collected with the enquette closed and have diujicoba to know the validity and reliabitas instrument. Result of data analysis indicate that there are influence which are positive and signifikan [of] [among/between] Graphical Media Use To Enthusiasm Learn The Education of Christian of Student of Class of VIII SMP Negeri 4 Tarutung of Tapanuli of Study Year 2018 with the coefficient determinasi ( r2) = 43.95% and test the signifikan influence obtained [by] Fhitung Ftabel [of] equal to 48,454,00, inferential thereby Ho refused and [Is] ha accepted Keyword : Graphical Media, Enthusiasm Learn